2019
DOI: 10.1002/jccs.201900124
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence studies of the interaction between chloramphenicol and nitrogen‐doped graphene quantum dots and determination of chloramphenicol in chicken feed

Abstract: Chloramphenicol (CAP) is a veterinary antibiotic that has been banned due to its severe side effects in humans. Through the application of manure, veterinary antibiotics can enter the soil, where they can be taken up by crops and vegetables and pose a potential health hazard to humans. Thus, it is highly desirable to develop a rapid and sensitive tool for on-site detection of CAP to ensure food safety and to control the abuse of antibiotics. To this end, nitrogen-doped graphene quantum dots (N-GQDs) were succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…On the contrary, the increase in temperature may cause the stability of the complex to decrease, thereby reducing the degree of static quenching. Comparing the Stern–Volmer quenching constant (KSV) according to the Stern–Volmer equation, the slope obtained for the data recorded at high temperature is lower than that at low temperature ( Table S4 ), which suggests that the mechanism of TAP-induced quenching of N, S-CDs excludes the possibility of dynamic collisions but was attributed to the formation of complexes [ 11 ]. The zeta potential of N, S-CDs was measured to be nearly −17.4 mV, which was attributed to the large number of nitrogen hydrogen bond and carbonyl groups present on the surface of N, S-CDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the increase in temperature may cause the stability of the complex to decrease, thereby reducing the degree of static quenching. Comparing the Stern–Volmer quenching constant (KSV) according to the Stern–Volmer equation, the slope obtained for the data recorded at high temperature is lower than that at low temperature ( Table S4 ), which suggests that the mechanism of TAP-induced quenching of N, S-CDs excludes the possibility of dynamic collisions but was attributed to the formation of complexes [ 11 ]. The zeta potential of N, S-CDs was measured to be nearly −17.4 mV, which was attributed to the large number of nitrogen hydrogen bond and carbonyl groups present on the surface of N, S-CDs.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence sensing detection method has been widely used due to excellent optical performance and high sensitivity in recent years. Several studies have shown that TAP detection techniques by semiconductor metal-quantum dot can obtain acceptable linear range and detection [ 11 , 12 ]. However, semiconductor quantum dots are primarily composed of II–VI or III–V metal elements, which still have biosecurity threats.…”
Section: Introductionmentioning
confidence: 99%
“…However, many poultry and cattle farmers continue to use CAP illegally. Tsai et al prepared N-GQDs from citric acid and urea by microwave-assisted synthesis and explored the fluorescence property of N-GQDs toward selective detection of CAP (Tsai et al, 2020). The sensing principle involves the π-π stacking interaction between the N-GQDs and CAP, which resulted in the quenching of N-GQD fluorescence.…”
Section: Veterinary Drug Residuesmentioning
confidence: 99%
“…4 However, CAP has tremendous toxic effects and is readily enriched in animals and humans, which may cause severe and irreversible myelosuppressive reactions resulting in aplastic anemia in humans and animals. 5 For this reason, CAP is explicitly prohibited for animal feeding and treatment in many countries, including Japan, America, and China. 6 Nevertheless, due to economic interests, some unscrupulous merchants still use CAP in animal husbandry and aquaculture, seriously endangering people's health.…”
Section: Introductionmentioning
confidence: 99%